2016
DOI: 10.3109/17518423.2016.1139009
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on classification of selected childhood neurodisabilities based on a review of literature

Abstract: None of the existing classifications addressed all the criteria. The heterogeneity associated with the selected neurodisabilities poses major challenges. Further work is required to establish improved classifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The descriptions of the levels of the Mini‐MACS are modified according to the age‐related activities of young children (<4y) with CP. The psychometric properties are essential criteria of utility …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The descriptions of the levels of the Mini‐MACS are modified according to the age‐related activities of young children (<4y) with CP. The psychometric properties are essential criteria of utility …”
mentioning
confidence: 99%
“…Exploring the predictive validity of the Mini‐MACS might help in selecting an early intervention. As stated in the literature, a stable classification with a clear and detailed focus on developmental pattern has the capacity to predict the course of a disorder …”
mentioning
confidence: 99%
“…The psychometric properties are essential criteria of utility. 4 The article by Eliasson et al 2 provides evidence of the reliability and validity of the Mini-MACS in classifying the manual abilities of young children with CP. The clear description of the levels, excellent reliability, and validity of the Mini-MACS enables its use by parents and therapists.…”
mentioning
confidence: 99%
“…As stated in the literature, a stable classification with a clear and detailed focus on developmental pattern has the capacity to predict the course of a disorder. 4 Further research on the predictive validity and clinical utility of the Mini-MACS may facilitate its use in clinical practice. A review on the MACS demonstrated that it is primarily used as a sample descriptor.…”
mentioning
confidence: 99%
See 1 more Smart Citation